Acute effects of maximal versus submaximal hurdle jump exercises on measures of balance, reactive strength, vertical jump performance and leg stiffness in youth volleyball players - Hammami, Raouf; Ben Ayed, Karim; Abidi, Manel; Werfelli, Hanen; Ajailia, Amira; Selmi, Walid; Negra, Yassine; Duncan, Michael; Rebai, Haithem; Granacher, Urs (Frontiers in Physiology, 2022)
Background: Although previous research in pediatric populations has reported performance enhancements following long-term plyometric training, the acute effects of plyometric exercises on measures of balance, vertical jump, reactive strength, and leg stiffness remain unclear. . Objectives: To determine the acute effects of maximal vs. submaximal hurdle jump exercise protocols executed during one training session on measures of balance, vertical jump, reactive strength, and leg stiffness in youth volleyball players. Materials and Methods: Thirty male youth volleyball players, aged 12 to 13 years, performed two plyometric exercise protocols in randomized order. In a within-subject design, the protocols were conducted under maximal (MHJ; 3 sets of 6 repetitions of 30-cm hurdle jumps) and submaximal (SHJ; 3 sets of 6 repetitions of 20-cm hurdle jumps) hurdle jump conditions. Pre- and post-exercise, balance was tested in bipedal stance on stable (firm) and unstable surfaces (foam), using two dependent variables (center of pressure surface area [CoP SA] and velocity [CoP V]). In addition, the reactive strength index (RSI) was assessed during countermovement maximal jumping and leg stiffness during side-to-side submaximal jumping. Testing comprised maximal countermovement jumps (CMJ). Results: Significant time-by-condition interactions were found for CoP SA firm (p <0.0001; d=0.80), CoP SA foam (p <0.0001; d=0.82), CoP V firm (p <0.0001; d=0.85), and CoP V foam (p <0.0001; d=0.83). Post-hoc analyses showed significant improvements for all balance variables from pretest to posttest for MHJ but not SHJ. All power tests displayed significant time-by-group interactions for CMJ (p<0.05; d=0.42), RSI (p<0.0001; d=1.58), and leg stiffness (p<0.001; d=0.78,). Post-hoc analyses showed significant pre-post CMJ (p<0.001, d= 1.95) and RSI (p<0.001, d=5.12) improvements for MHJ but not SHJ. SHJ showed larger pre-post improvements compared with MHJ for leg stiffness (p<0.001; d=3.09). Conclusions: Due to the importance of balance and muscle strength/power for overall competitive performance in volleyball, these results suggest that young volleyball players should implement dynamic plyometric protocols involving maximal and submaximal stretch-shortening cycle hurdle exercises during warm-up to improve subsequent balance and muscle strength/power.